High‐density lipoprotein‐associated paraoxonase‐1 activity for prediction of adverse outcomes in outpatients with chronic heart failure. (7th February 2017) - Hammadah, Muhammad; Kalogeropoulos, Andreas P.; Georgiopoulou, Vasiliki V.; Weber, Malory; Wu, Yuping; Hazen, Stanley L.; Butler, Javed; Tang, W.H. Wilson
Abstract: Aims: Decreased arylesterase (ArylE) activity of paraoxonase‐1, a HDL‐associated protein with anti‐inflammatory and antioxidant properties, has been associated with increased risk of cardiac events in patients with ischaemic heart failure (HF). We aim to investigate the prognostic significance of changes in serum ArylE activity over time. Methods and results: We examined the association between baseline and follow‐up serum ArylE activity and HF outcomes (death, cardiac transplantation, or ventricular assist device implantation) in 299 patients with HF enrolled in a prospective cohort study from January 2008 to July 2009, with 145 patients having available follow‐up levels at 1 year. A significant drop in ArylE activity on follow‐up was defined as a drop of ≥25% vs. baseline levels. Mean baseline and follow‐up ArylE activity levels were 110.6 ± 29.9 µmol/min/mL and 106.2 ± 29.9 µmol/min/mL, respectively. After a mean follow‐up of 2.8 ± 1.1 years, low baseline ArylE activity was associated with increased risk of adverse HF events [hazard ratio (HR; lowest vs highest tertile) 2.6, 95% confidence interval (CI) 1.3–5.5, P = 0.01] and HF‐related hospitalization [incidence rate ratio (lowest vs. highest tertile) 2.1, 95% CI 1.2–4.1, P = 0.016], which remained significant after adjustment for age, male gender, systolic blood pressure, diabetes, creatinine clearance, CAD, and HDL‐cholesterol levels. Patients who had a significant drop in ArylE activity on follow‐up ( n = 18) had a significantly increased risk of HF events (HR 4.9, 95% CI 1.6–14.6, P = 0.005), even after adjustment for baseline levels of ArylE activity. Conclusions: Reduced baseline ArylE activity and decreased levels on follow‐up are associated with adverse outcomes in stable outpatients with HF.